Vertical grammar of parallelism in Biblical Hebrew - Tsumura, David Toshio (Ancient Israel and its literature ;, 2023)
"An essential resource for sound exegesis of biblical poetry While previous books on parallelism have focused almost exclusively on semantic classification, in his new book David Toshio Tsumura focuses on the grammatical and phonetic aspects as well. In particular, he defines and illustrates the vertical grammatical relationship between parallel lines. Readers will master how to read Biblical Hebrew poetry effectively by focusing on the basic linguistic features of word order, parallelistic structure, and rhetorical devices. For the benefit of nonspecialists, all Hebrew poems are given in accessible transliteration. This book is an indispensable companion to the Hebrew Bible for both beginners and experienced scholars."--